Highly efficient and scalable chemoenzymatic syntheses of (R)- and (S)-lactaldehydes. Issue 2 (6th November 2015) - Vogel, M. A. K.; Burger, H.; Schläger, N.; Meier, R.; Schönenberger, B.; Bisschops, T.; Wohlgemuth, R.
Abstract : Biocatalytic asymmetric reductions have been key steps in the synthesis of 1, 1-dimethoxy-2-propanone, catalyzed by suitable ketoreductases to ( S )- and ( R )-1, 1-dimethoxy-2-propanol, obtained in ≥99.9% ee and excellent yield. Removal of the protecting group gave the ( S )- and ( R )-lactaldehydes in excellent yield and purity. Abstract : Biocatalytic asymmetric reductions have been key steps in the enantioselective reduction of 1, 1-dimethoxy-2-propanone, catalyzed by suitable ketoreductases, to enantiomerically pure ( S )- and ( R )-1, 1-dimethoxy-2-propanols, obtained in ≥99.9% ee and excellent yield. Removal of the protecting group gave the ( S )- and ( R )-lactaldehydes in high yield and excellent enantiomeric and chemical purity.